ธรรมาภิบาลในการจัดการทรัพยากรน้ำภายใต้อิทธิพลของระบบตลาด : ศึกษากรณีการจัดสัมปทานน้ำในจังหวัดระยอง - สันต์ชัย รัตนะขวัญ (จุฬาลงกรณ์มหาวิทยาลัย, 2008)
This research aims to study the characteristics of governance in water management in Rayong Province under the condition that the private sector has concession to deliver water to industrial sector. This includes also the identification of its impacts on stakeholders. This study finally analyses the conditions improving governance in water management. The thesis uses qualitative method. Information was gathered from documents and in-depth interviews. Key informants are from government and private sector as well as from the social movements. The thesis finds that the government s development policies, which prioritizes industrial development in Rayong Province, affect the characteristic of governance in water management. When the government initiated private sector, EAST WATER co.ltd., to deliver water to industrial sector, it has brought a new actor in water management. This reflects upon the management that is based more on the economic efficiency and effectiveness dimension of governance. In addition, water management which overlooks public participation and information accessibility leads to the lack of fairness in the eyes of the stakeholders in agricultural and household sector especially when facing the crisis of water scarcity. To promote good governance in water management need an authentic participation of stakeholders which can be achieved by legal and institutional reform. It is also imperative to define clearly the fairness dimension of water management.